2019
DOI: 10.1080/10494820.2019.1572628
|View full text |Cite
|
Sign up to set email alerts
|

Flow experiences in personalised e-learning environments and the role of gender and academic performance

Abstract: Meseguer-Artola, A. & Rodríguez-Ardura, I. (2019). Flow experiences in personalised e-learning environments and the role of gender and academic performance. Interactive Learning Environments, (), 1-24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 133 publications
(146 reference statements)
2
22
0
Order By: Relevance
“…The finding further showed that increased e-learning engagement weakens the impact of flow on continuance intention to use the learning management system. The negative interaction of the finding supports the proposition that the mixed relationship between flow and continued intention in past studies is caused by unexamined moderators, as negative interaction can significantly attenuate the relationship if the samples collected were biased towards a highly engaging group (Hong et al, 2019;Rodríguez-Ardura & Meseguer-Artola, 2019). Since there is a non-significant relationship between e-learning engagement and continuance intention as depicted in Table 5, the weakening effect of flow on continuance intention is not caused by the moderator decreasing the level of continuance intention.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The finding further showed that increased e-learning engagement weakens the impact of flow on continuance intention to use the learning management system. The negative interaction of the finding supports the proposition that the mixed relationship between flow and continued intention in past studies is caused by unexamined moderators, as negative interaction can significantly attenuate the relationship if the samples collected were biased towards a highly engaging group (Hong et al, 2019;Rodríguez-Ardura & Meseguer-Artola, 2019). Since there is a non-significant relationship between e-learning engagement and continuance intention as depicted in Table 5, the weakening effect of flow on continuance intention is not caused by the moderator decreasing the level of continuance intention.…”
Section: Discussionsupporting
confidence: 71%
“…According to Schindler et al (2017), these computer-based learning activities represent a technology factor that affects students' engagement and directly relates to their flow experience (Sahid et al, 2016). For instance, goal-oriented processes are more conducive to developing flow than experiential types (Novak et al, 2003) and e-learning activities that challenge student abilities to reach new levels are conducive to triggering flow (Rodríguez-Ardura & Meseguer-Artola, 2019). A learner who engages with more learning activities is more likely to encounter flow experiences.…”
Section: E-learning Engagementmentioning
confidence: 99%
“…Women find peer interaction and a shared learning space more comfortable for effective e-learning. This social predisposition may lead female students to become more involved in or connected with other learners, thanks to a greater sense of peer and instructor presence [34]. Accordingly, we expected to observe gender discrepancies in e-learning education assessment.…”
Section: Additional Analysismentioning
confidence: 94%
“…Research must not only focus on the benefits of e-learning (and e-tutors) in overcoming limitations at universities but also explore the characteristics of participants who are actively involved in e-learning initiatives. The analysis should also consider how these characteristics may influence e-learning outcomes [34]. Researchers are becoming especially interested in e-learning gender issues.…”
Section: Additional Analysismentioning
confidence: 99%
See 1 more Smart Citation